USE OF IMAGE MEDIA IMPROVES STUDENT LEARNING OUTCOMES SCIENCE SUBJECTS CLASSIFICATION OF ANIMALS BASED ON THEIR FOOD TYPES IN CLASS V OF ELEMENTARY SCHOOL - Rakasita, Ely; Azmi, Ulil (Academic Journal Research, 2024)
Objective: This study aims to improve student learning outcomes on the topic of animal classification based on food type at SDN 15 Pulau Rimau, addressing the low achievement caused by traditional teaching methods. Method: A classroom action research approach was employed, utilizing scientific models and visual media to enhance understanding and engagement. The research was conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. Data were collected through descriptive analysis, in collaboration with the classroom teacher. Results: The use of scientific models and image media significantly improved student participation and learning outcomes. Observations during both cycles showed increased student engagement and a better grasp of the material. Novelty: This study contributes to the field by demonstrating the effectiveness of combining scientific teaching models with visual aids to foster active learning and improve academic performance, particularly in science education.